2014
DOI: 10.1039/c3nr05858a
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic charge transport in large single crystals of π-conjugated organic molecules

Abstract: The electronic properties of organic semiconductors depend strongly on the nature of the molecules, their conjugation and conformation, their mutual distance and the orientation between adjacent molecules. Variations of intramolecular distances and conformation disturb the conjugation and perturb the delocalization of charges. As a result, the mobility considerably decreases compared to that of a covalently well-organized crystal. Here, we present electrical characterization of large single crystals made of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 22 publications
(33 reference statements)
0
35
0
Order By: Relevance
“…Their procedure allowed control over the number of density, size, and internal structure of these crystals . In addition, they showed that charge transport through the single crystal was anisotropic . The P3HT single crystals absorbed light at higher wavelengths compared to spin‐cast films and thus a remarkable red shift occurred .…”
Section: Introductionmentioning
confidence: 99%
“…Their procedure allowed control over the number of density, size, and internal structure of these crystals . In addition, they showed that charge transport through the single crystal was anisotropic . The P3HT single crystals absorbed light at higher wavelengths compared to spin‐cast films and thus a remarkable red shift occurred .…”
Section: Introductionmentioning
confidence: 99%
“…Hourani et al designed an organic field-effect transistor (OFET) composed of regioregular octamer of 3-hexyl-thiophene (3HT) 8 showing anisotropic charge transport properties. [97] In the p-p stacking direction of this polymeric semiconductor (along the long axis of the single crystal with mobility of 10 23 cm 2 V 21 s 21 ) the charge transport is smaller than that along the molecular axis (in the direction of the thickness of the single crystal with mobility of 0.5 cm 2 V 21 s 21 ). Therefore, the pp stacking interaction controls charge carrier mobility in these polymeric semiconductors.…”
Section: Review Wwwq-chemorgmentioning
confidence: 99%
“…In the realm of semiconductive polymers, large single rectangular crystals of 3-hexyl thiophene (3HT) 8 [35,36], nanowires of conjugated poly(p-phenylene ethynylene) derivatives [37], poly(3-hexyl thiophene) (P3HT) nanowhiskers [38], one-dimensional (1D) microwire P3HT single crystals [39], and self-organized two-dimensional (2D) P3HT supramolecules [40,41] were reported. Nascent lateral habits of solution-grown single crystals [42], surface-patterned single crystals [43][44][45][46][47], and conductive-dielectric-conductive single crystals [48][49][50] have also been reported.…”
Section: Introductionmentioning
confidence: 99%